A New Series of Antileukemic Agents: Design, Synthesis, In Vitro and In Silico Evaluation of Thiazole-Based ABL1 Kinase Inhibitors - Zeytün, Ebru; Altıntop, Mehlika D.; Sever, Belgin; Özdemir, Ahmet; Ellakwa, Doha E.; Ocak, Zeynep; Ciftci, Halil I.; Otsuka, Masami; Fujita, Mikako; Radwan, Mohamed O. (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: After the approval of imatinib, more than 25 antitumor agents targeting kinases have been approved, and several promising candidates are at various stages of clinical evaluation. Objectives: Due to the importance of the thiazole scaffold in targeted anticancer drug discovery, the goal of this work is to identify new thiazolyl hydrazones as potent ABL1 kinase inhibitors for the management of Chronic Myeloid Leukemia (CML). Methods: New thiazolyl hydrazones (2a-p) were synthesized and investigated for their cytotoxic effects on the K562 CML cell line. Compounds 2h, 2j and 2l showed potent anticancer activity against K562 cell line. The cytotoxic effects of these compounds on other leukemia (HL-60, MT-2 and Jurkat) and HeLa human cervical carcinoma cell lines were also investigated. Furthermore, their cytotoxic effects on Mitogen-Activated Peripheral Blood Mononuclear Cells (MA-PBMCs) were evaluated to determine their selectivity. Due to its selective and potent anticancer activity, compound 2j was benchmarked for its apoptosis-inducing potential on K562 cell line and inhibitory effects on eight different Tyrosine Kinases (TKs), including ABL1 kinase. In order to investigate the binding mode of compound 2j into the ATP binding site of ABL1 kinase (PDB: 1IEP), a molecular docking study was conducted using MOE 2018.01 program. The QikProp module of Schrödinger’s Molecular modelling package was used to predict the pharmacokinetic properties of compounds 2a-p. Results: 4-(4-(Methylsulfonyl)phenyl)-2-[2-((1,3-benzodioxol-4-yl)methylene)hydrazinyl]thiazole (2j) showed antiproliferative activity against K562 cell line with an IC50 value of 8.87±1.93 μM similar to imatinib (IC50= 6.84±1.11μM). Compound 2j was found to be more effective than imatinib on HL-60, Jurkat and MT-2 cells. Compound 2j also showed cytotoxic activity against HeLa cell line similar to imatinib. The higher selectivity index value of compound 2j than imatinib indicated that its antiproliferative activity was selective. Compound 2j also induced apoptosis in K562 cell line more than imatinib. Among eight TKs, compound 2j showed the strongest inhibitory activity against ABL1 kinase enzyme (IC50= 5.37±1.17μM). According to molecular docking studies, compound 2j exhibited high affinity to the ATP binding site of ABL1 kinase, forming significant intermolecular interactions. On the basis of in silico studies, this compound did not violate Lipinski's rule of five and Jorgensen's rule of three. Conclusion: Compound 2j stands out as a potential orally bioavailable ABL1 kinase inhibitor for the treatment of CML.
Keywords: chronic myeloid leukemia